Release of GTP exchange factor mediated down-regulation of abscisic acid signal transduction through ABA-induced rapid degradation of RopGEFs - Li, Zixing; Waadt, Rainer; Schroeder, Julian I. (PLoS biology, 2016)
The phytohormone abscisic acid (ABA) is critical to plant development and stress responses. Abiotic stress triggers an ABA signal transduction cascade, which is comprised of the core components PYL/RCAR ABA receptors, PP2C-type protein phosphatases, and protein kinases. Small GTPases of the ROP/RAC family act as negative regulators of ABA signal transduction. However, the mechanisms by which ABA controls the behavior of ROP/RACs have remained unclear. Here, we show that an Arabidopsis guanine nucleotide exchange factor protein RopGEF1 is rapidly sequestered to intracellular particles in response to ABA. GFP-RopGEF1 is sequestered via the endosome-prevacuolar compartment pathway and is degraded. RopGEF1 directly interacts with several clade A PP2C protein phosphatases, including ABI1. Interestingly, RopGEF1 undergoes constitutive degradation in pp2c quadruple abi1/abi2/hab1/pp2ca mutant plants, revealing that active PP2C protein phosphatases protect and stabilize RopGEF1 from ABA-mediated degradation. Interestingly, ABA-mediated degradation of RopGEF1 also plays an important role in ABA-mediated inhibition of lateral root growth. The presented findings point to a PP2C-RopGEF-ROP/RAC control loop model that is proposed to aid in shutting off ABA signal transduction, to counteract leaky ABA signal transduction caused by “monomeric” PYL/RCAR ABA receptors in the absence of stress, and facilitate signaling in response to ABA.